Heritable arrhythmias: insight into molecular physiology from the long QT syndrome - Kass, Robert (Henry Stewart Talks, 2011)
The long QT syndrome, LQTS: genetic linkage to ion channel genes, Molecular IKS signaling complex and long QT syndrome, IKS subunits: KCNQ1 and KCNE1, KCNQ1 mutations and IKS regulation, Yotiao: an additional component, Mutations in Yotiao linked to LQTS, IKS and other cardiac disorders, The location of KCNE1 in the IKS channel, Control of KCNQ1 gating by KCNE1, Alteration of voltage sensor movement by KCNE1, KCNE1/KCNQ1 stoichiometry and its implications